Distribusi Pendapatan Usahatani Padi Sawah (Oriza sativa L) di Kecamatan Aikmel Kabupaten Lombok Timur - Dwi Haryati Ningsih; Muhammad Anwar (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Agriculture is the basis for industrial development and is a pilot project for a country's economic development strategy. Even though its role is small, it impacts community welfare, especially providing food. This research aims to determine the costs and distribution of income from rice farming. The study was conducted in Aikmel District, East Lombok Regency, from August to October 2022. The number of respondents was 44, distributed to each village using proportional sampling to 9 villages, which were considered representative based on the most significant number of farmers and area of rice fields, namely Toya Village with six people, East Aikmel 6 people, East Kalijage 5 people, Kembang Kerang 5 people, Kalijage 5 people, Aikmel West 4 people, Aikmel North 4 people, Kembang Kerang Daye 4 people, and Keroya 4 people. The selection of respondents in each village was done using purposive sampling. Data analysis uses cash flow analysis and Gini ratio analysis. The research results showed that production costs amounted to IDR15,004,910 per area of cultivated land or IDR18,540,185 per hectare, the income value (Net Return) received was IDR13,303,772 per area of developed land or IDR 16,438,248 per hectare. The level of income distribution for rice farming in Aikmel District is that most people earn between 5-9.9 million, totaling 22 people or (50.00%), and based on the Gini coefficient of 0.246, it can be said that income inequality is at a low level.